A ética na visão literária de Machado de Assis – Contos “A cartomante” e “A carteira” - SANTANA, Marcilene da Silva (2023)
Such research has the theme : Ethics in the literary vision of Machado de Assis - tales "The Wallet” and “The Fortune Teller" addressing a case study through observational and monographic methods in order to answer the following problems: How to address the ethical issue using literature as an ally in the stories "the Fortune Teller" and "the Portfolio" Machado de Assis? How can we awaken a love of reading in students using the tales "The Fortune Teller" and "The Portfolio" Machado de Assis? Therefore, we use as theoretical Alfredo Bosi (2012), Antonio Candido (1993), Moisés Massaud (2007) , Roberto Schwarz (2012a, 2012b), Álvaro Valls (1994), among others. It was observed during the study, some factors interfere in the process of learning Portuguese discipline of students of the 8th ano/09 Private Preschool and Elementary Education "Sementinha Educational Center of Knowledge", among them the lack of a methodology to arouse the interest of students and the lack of dynamics and planning involving interdisciplinary with cross-cutting issues, in particular ethics.